SENTRA KERAJINAN KERAMIK DENGAN PENERAPAN ARSITEKTUR EKSPRESIONISME DI JALAN IR. HAJI JUANDA REMPOA, TANGERANG SELATAN - Isra Wahyudin; Mieke Choandi (Jurusan Arsitektur dan Perencanaan, 2022)
Jalan Ir. Haji Juanda is the main access that connects the city of South Tangerang with South Jakarta, resulting in high density and potential opportunities for business people. Seeing business opportunities and interest in fine art objects, in 1974 a fine art shop appeared called an